Introduction to Mathematical Logic and Set Theory - LŐRINCZI , Ábel; MARCUS, Andrei (Presa Universitară Clujeană, 2025)
Mathematical logic is part of Mathematics and of Logic. Its role is to rigorously define the idea of the truth value of a statement and to explore the application of formal (symbolic) logic methods in different branches of mathematics. Also, mathematical logic deals with the application of mathematical methods and techniques to the study of formal logic.